2011
DOI: 10.1080/01446193.2010.521759
|View full text |Cite
|
Sign up to set email alerts
|

A typology of operational approaches for stakeholder analysis and engagement

Abstract: Stakeholder analysis and engagement are the main tasks in stakeholder management. To identify operational approaches for stakeholder analysis and engagement, six interviews and a questionnaire survey were conducted in Hong Kong, and an additional fifteen interviews were held in Australia. The main finding is a typology of practical approaches for practitioners in construction. A total of thirty approaches are comprised in the typology, and they are classified by application. To test the usefulness of the typol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 27 publications
0
63
0
Order By: Relevance
“…Urgency refers to how urgent stakeholders' claims are; such urgent claims are based on time sensitivity and criticality (Mitchell et al, 1997). The importance of urgency in project field was also confirmed by other researchers (Bourne & Walker, 2006;Yang, Shen, Bourne, et al, 2011). This study will retain urgency for further assessment.…”
Section: Stakeholder Influential Attributesmentioning
confidence: 53%
See 2 more Smart Citations
“…Urgency refers to how urgent stakeholders' claims are; such urgent claims are based on time sensitivity and criticality (Mitchell et al, 1997). The importance of urgency in project field was also confirmed by other researchers (Bourne & Walker, 2006;Yang, Shen, Bourne, et al, 2011). This study will retain urgency for further assessment.…”
Section: Stakeholder Influential Attributesmentioning
confidence: 53%
“…Bourne & Walker (2006) replaced legitimacy with proximity claiming it ignores stakeholders beyond contractual rights. Yang, Shen, Bourne, et al (2011) also replaced legitimacy with proximity due to its complication and restriction.…”
Section: Stakeholder Influential Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of stakeholder management in construction projects have been emphasized and reported by a number of studies according to Yang, Shen Ho, Drew & Chan [19]. Yang et al [20] further posit that the construction industry has failed dismally in effectively managing stakeholders in the last decade. Although studies conducted within the industry has shown that some of the challenges of stakeholder management in construction projects include: inadequate engagement of stakeholders, project managers having unclear objectives of stakeholder management, difficulty to identify the "invisible" stakeholder, and inadequate communication with stakeholders.…”
Section: Stakeholder Managementmentioning
confidence: 99%
“…In a research by Yang et al [20] conducted on construction projects in Hong Kong, the top three critical success factors identified as effective in stakeholder management are: managing stakeholders with social responsibilities namely: economic, legal, environmental and ethical; exploring the stakeholders' needs and constraints to the project, and communicating with and engaging stakeholders properly and frequently.…”
Section: Stakeholder Managementmentioning
confidence: 99%